In vivo theranostics with near-infrared-emitting carbon dots—highly efficient photothermal therapy based on passive targeting after intravenous administration. Issue 1 (December 2018) - Bao, Xin; Yuan, Ye; Chen, Jingqin; Zhang, Bohan; Li, Di; Zhou, Ding; Jing, Pengtao; Xu, Guiying; Wang, Yingli; Holá, Kateřina; Shen, Dezhen; Wu, Changfeng; et al.
Abstract Carbon dots that exhibit near-infrared fluorescence (NIR CDs) are considered emerging nanomaterials for advanced biomedical applications with low toxicity and superior photostability and targeting compared to currently used photoluminescence agents. Despite progress in the synthesis of NIR CDs, there remains a key obstacle to using them as an in vivo theranostic agent. This work demonstrates that the newly developed sulfur and nitrogen codoped NIR CDs are highly efficient in photothermal therapy (PTT) in mouse models (conversion efficiency of 59%) and can be readily visualized by photoluminescence and photoacoustic imaging. The real theranostic potential of NIR CDs is enhanced by their unique biodistribution and targeting. Contrary to all other nanomaterials that have been tested in biomedicine, they are excreted through the body's renal filtration system. Moreover, after intravenous injection, NIR CDs are accumulated in tumor tissue via passive targeting, without any active species such as antibodies. Due to their accumulation in tumor tissue without the need for intratumor injection, high photothermal conversion, excellent optical and photoacoustic imaging performance, and renal excretion, the developed CDs are suitable for transfer to clinical biomedical practice. Carbon dots: Lighting up for cancer therapy and diagnosis 'Carbon dot' nanoparticles composed largely of carbon, but doped with sulfur and nitrogen, accumulate within cancer cells and absorb near-infrared laser light to generate cell-killing heat. The procedure was developed and tested by researchers in China and the Czech Republic, led by Songnan Qu at the Changchung Institute of Optics, Fine Mechanics and Physics. The nanoparticles accumulated passively in tumors after intravenous injection into mice, with no specific targeting methods required. Tumors were effectively eradicated by the highly efficient conversion of the light energy into heat. The nanoparticles are biocompatible and are eventually excreted harmlessly in urine. In addition to the potential for treating cancer, diagnosis can also be assisted using the particles' fluorescent properties. This combination of therapy and diagnosis – 'theranostics' – can now be further developed and explored for use in patients.